The Mediating Effect of Customer Satisfaction on the Relationship Between Service Recovery Performance Factors and Business Growth among Bangladesh Garment Manufacturers - Hasan, Sheikh Md Kamrul (2021)
As of late, business growth is being sensed as one of the greatest challenges for Bangladesh garment industry in order to gain competitive advantage in global market because many garment factories have been shutting down since last few years. However, the owners of garment manufacturers are deeming intensely regarding the impact of service recovery phenomenon on the most topical and imperative issue- company business growth. The purpose of this opportune study is twofold; firstly to examine the relationship between influential factors of service recovery performance (SRP) and business growth, secondly to examine the mediating effect of customer satisfaction on relationships between SRP factors and business growth in context of Bangladesh garment industry. Based on literature review, a conceptual model has been developed for a cross-sectional sample survey study. Primary data were collected following simple random sampling method from 354 different garment factories in Bangladesh. The partial least squares path modeling (PLS-SEM) approach was used by Smart PLS 3.2 software for data analysis and necessary hypothesis inferences. The results revealed that most of the SRP factors directly influence company business growth, and customer satisfaction plays mediating role on relationships between some specific SRP factors (top management commitment, role ambiguity, job satisfaction and customer’s characteristics) and company business growth. The findings of this research contribute both theoretically and practically, and append the knowledge how garment factories can formulate new strategy and management practice to ensure sustained business growth. Hitherto this is the first study that investigated and established the relationship among SRP factors, business growth and customer satisfaction in context of garment manufacturing industry.